N,N′-dihydrotetraazapentacenes (DHTA) in thin film transistors - Paulus, Fabian; Lindner, Benjamin; Reiß, Hilmar; Rominger, Frank; Leineweber, Andreas; Vaynzof, Yana; Sirringhaus, Henning; Bunz, Uwe H. F. (Journal of materials chemistry. C, Materials for optical and electronic devices, 2015)
The synthesis and structural properties of three N,N′-dihydrotetraazapentacenes (DHTA) are described. The different substitution pattern (H, F, Cl) of the dihydrotetraazapentacene body exhibited a significant effect on the optical, electronic and morphological properties of the derivatives in thin films. The synthesised materials were investigated as active layers in top gate/bottom contact (BC/TG) transistors. The transistor performance of the dichlorinated derivative was almost independent on the processing conditions with an average hole mobility of ∼0.04 cm2 V−1 s−1 and best mobility values ranging from 0.07 to 0.11 cm2 V−1 s−1. Each of the three derivatives was found to exhibit an individual packing motif in solution grown crystals, determined by single crystal X-ray analysis. Surprisingly, for all three materials a different polymorph formed in spin cast films explaining the observed morphology and FET performance.
Published on 18 December 2014
Gesehen am 20.07.2020